High Carbon Steel Plate
A high carbon steel plate with a controlled microstructure and chemical composition enhances workability for complex automotive parts by optimizing ferrite and carbide distribution, addressing the challenge of processing complexity.
Patent Information
- Application Number
- JP2020157630
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-18
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-09-18
AI Technical Summary
High carbon steel sheets face challenges in achieving sufficient workability for complex processing due to increased demand in automotive parts requiring smaller and more complex shapes.
A high carbon steel plate with a controlled microstructure composed of 70-95% ferrite and carbides, where carbides have an average aspect ratio of 3.0 or less and an average equivalent circular diameter of 0.40 to 2.00 μm, with 70% or more present at grain boundaries, and a specific chemical composition to enhance workability.
The solution provides a high carbon steel plate with improved workability, enabling complex processing and maintaining strength through controlled ferrite and carbide distribution.
Smart Images

Figure 0007606070000001 
Figure 0007606070000002 
Figure 0007606070000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high carbon steel sheet. [Background technology]
[0002] Conventionally, high carbon steel sheets with a C content of 0.60 mass % or more have been widely used as materials for drive system parts such as clutches and gears in automobiles. When manufacturing a part of a predetermined shape from a high carbon steel sheet, the high carbon steel sheet is generally subjected to cold working and heat treatment, and therefore the high carbon steel sheet is required to have workability.
[0003] In recent years, the electrification of automobiles has progressed, and automobile parts are required to be smaller and have more complex shapes in order to secure space and reduce weight. Accordingly, the high carbon steel sheets used as the material for these parts are required to have further improved formability in order to be able to carry out more complex processing.
[0004] Patent Document 1 discloses that a high-carbon hot-rolled steel sheet having excellent stretch flangeability and hardness uniformity in the thickness direction can be obtained by controlling the volume ratio of carbides having a grain size of less than 0.5 μm to the total volume of carbides to 15% or less. Patent Document 1 also discloses a manufacturing method for obtaining such a steel sheet, which includes the steps of hot-rolling a steel having a composition containing 0.2 to 0.7 mass% of C at a finishing temperature of (Ar3 transformation point - 20°C) or more to obtain a hot-rolled steel sheet, cooling the hot-rolled steel sheet to a temperature of 650°C or less at a cooling rate of 60°C / sec or more and less than 120°C / sec, coiling the cooled hot-rolled steel sheet at a coiling temperature of 600°C or less, and annealing the coiled hot-rolled steel sheet at an annealing temperature of 640°C or more and Ac1 transformation point or less.
[0005] Patent Document 2 discloses a medium carbon steel plate having excellent cold workability and hardenability, characterized in that the medium carbon steel plate contains, by mass%, 0.10 to 0.80% C, 0.01 to 0.35% Si, 0.3 to 2.0% Mn, 0.005 to 0.03% P, 0.0001 to 0.01% S, 0.005 to 0.10% Al, and 0.001 to 0.01% N, with the balance being Fe and unavoidable impurities, has an average carbide diameter of 0.4 μm or less, a spheroidization rate of carbides of 90% or more, a yield ratio of 60% or less, and further has quench hardenability that hardens to 500 HV or more after quenching, and a manufacturing method thereof. Patent Document 2 describes how cold rolling with a light reduction adds strain to the structure obtained in the hot-rolled sheet, promoting grain growth and recrystallization, and thus providing a medium carbon steel sheet with excellent cold workability due to a low yield ratio and extremely softness, and also precipitating fine carbides with a high spheroidization rate, thereby providing a medium carbon steel sheet with sufficient quench hardening ability under any quenching conditions.
[0006] However, in recent years, there has been a demand for high carbon steel sheets having formability capable of withstanding more complicated processing. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2007-039796 A [Patent Document 2] JP 2013-057114 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in view of the above problems. An object of the present invention is to provide a high carbon steel sheet having excellent workability. [Means for solving the problem]
[0009] The gist of the present invention is as follows. [1] In mass%, C: 0.60~1.30%, Si: 0.010~0.500%, Mn: 0.35~1.00%, Al: 0.0010~0.0500%, Cr: 0.010~0.600%, Mo: 0.00 5~0.050%, P:0~0.100%, S:0~0.100%, N:0~0.0100%, Ni:0~3.000%, Cu:0~3.000%, Co:0~3.000%, Nb:0~1.000%, Ti The alloy has a chemical composition of: 0-1.000%, V: 0-1.0000%, B: 0-0.0100%, Sn: 0-1.000%, W: 0-1.000%, Ca: 0-0.3000%, REM: 0-0.300%, and the balance: Fe and impurities, and the microstructure is composed of 70-95% by area ratio of ferrite and carbides, and the carbides have an average aspect ratio of 3.0 or less and an average equivalent circle diameter of 0.40-2.00 μm. the law of nature , In terms of number, 70% or more of the carbides are present at grain boundaries. , high carbon steel plate 。 [ 2 ] the {100} <011> ~{223} <110> The average X-ray random intensity ratio of the orientation group is 7.0 or less. [1] The high carbon steel plate described above. Effect of the Invention
[0010] According to the present invention, a high carbon steel sheet having excellent workability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present inventors have investigated the cold workability of high carbon steel sheets, and as a result, have obtained the following new findings. Cold workability is highly dependent on the strength of the steel sheet. Therefore, high carbon steel sheets to be cold worked are controlled to have a structure containing ferrite by annealing, etc. Annealed materials obtained by annealing high carbon steel sheets are mainly composed of ferrite and carbides such as cementite. The strength of steel sheet depends on the grain size of ferrite and cementite. Therefore, to improve workability (softening), it is effective to coarsen the grain size of ferrite or cementite. By controlling the structure before annealing in the hot rolling process, the cementite in the structure after annealing becomes coarse, improving workability. The present invention has been made based on the above findings.
[0012] Hereinafter, a high carbon steel sheet according to one embodiment of the present invention (high carbon steel sheet according to this embodiment) will be described in detail. First, the reasons for limiting the chemical composition of the high carbon steel sheet according to this embodiment will be described. In the following numerical ranges separated by "~" the lower and upper limits are included. However, values indicated as "less than" and "more than" are not included in the numerical range. All % for chemical composition indicates mass %.
[0013] C: 0.60-1.30% Carbon (C) is an element effective for increasing the strength of quenched steel. C is also an element that forms carbides to control the work hardening behavior of the steel sheet. The high carbon steel sheet according to the present embodiment is subjected to heat treatment such as quenching or quenching and tempering after forming to ensure the strength or toughness required for various parts. The high carbon steel sheet according to the present embodiment is treated in this way and is used, for example, as drive system parts such as gears and clutches of automobiles, or parts constituting blades such as saws. If the C content is too low, the strength improvement effect by quenching cannot be obtained sufficiently, and the strength when made into a part is insufficient. Therefore, the C content is set to 0.60% or more. The C content is preferably 0.65% or more, more preferably 0.70% or more. On the other hand, if the C content is too high, the strength of the steel sheet increases too much and the workability decreases. Therefore, the C content is set to 1.30% or less. The C content is preferably 1.20% or less.
[0014] Silicon: 0.010 to 0.500% Silicon (Si) is an element that acts as a deoxidizer for steel. In addition, Si is an element that increases the strength of steel by solid solution strengthening. If the Si content is too low, the strength of the parts made into parts will be insufficient. Therefore, the Si content is set to 0.010% or more. The Si content is preferably 0.050% or more, and more preferably 0.080% or more. On the other hand, if the Si content is too high, workability deteriorates due to solid solution strengthening, so the Si content is set to 0.500% or less, preferably 0.450% or less, and more preferably 0.400% or less.
[0015] Mn: 0.35-1.00% Manganese (Mn) is an element effective in increasing the strength of hardened steel. If the Mn content is too low, this effect is not sufficiently obtained. In addition, the desired carbides cannot be obtained. Therefore, the Mn content is set to 0.35% or more. The Mn content is preferably 0.40% or more, and more preferably 0.45% or more. On the other hand, if the Mn content is too high, the workability of the steel sheet decreases. Therefore, the Mn content is set to 1.00% or less. The Mn content is preferably 0.90% or less, and more preferably 0.80% or less.
[0016] Al: 0.0010~0.0500% Aluminum (Al) is an element that acts as a deoxidizer for steel. If the Al content is too low, the average aspect ratio, equivalent circle diameter, grain boundary ratio, and / or texture of carbides cannot be obtained as desired. In addition, coarse oxides are generated, reducing toughness. Therefore, the Al content is set to 0.0010% or more. On the other hand, if the Al content is too high, coarse oxides are formed and the workability of the steel sheet is reduced, so the Al content is set to 0.0500% or less.
[0017] Cr: 0.010~0.600% Chromium (Cr) is an effective element for increasing the strength of hardened steel. If the Cr content is too low, the strength improvement is not achieved, and the strength of the parts will be insufficient. Therefore, the Cr content is set to 0.010% or more. On the other hand, if the Cr content is too high, the carbides will not have the desired form, or the strength of the steel sheet will increase, decreasing the workability, so the Cr content is set to 0.600% or less.
[0018] Mo: 0.005 to 0.050% Molybdenum (Mo) is an element that is effective in increasing the strength of hardened steel. It is also an element that affects the formation of carbides. If the Mo content is too low, the strength improvement effect is not obtained, and the strength of the parts when made into parts is insufficient. Therefore, the Mo content is set to 0.005% or more. On the other hand, if the Mo content is too high, the carbides will not have the desired form, or the strength of the steel sheet will increase, decreasing the workability, so the Mo content is set to 0.050% or less.
[0019] P: 0~0.100% Phosphorus (P) is an impurity. P increases the strength of steel sheet, but at the same time, it segregates at grain boundaries and reduces workability. Therefore, the P content is set to 0.100% or less. The lower the P content, the better, and 0% is acceptable, but reducing the P content to less than 0.001% significantly increases refining costs. Therefore, the P content may be set to 0.001% or more.
[0020] S: 0~0.100% Sulfur (S) is an impurity. S is an element that forms nonmetallic inclusions such as MnS. Such nonmetallic inclusions deteriorate the workability of steel sheets. Therefore, the S content is set to 0.100% or less. It is preferable that the S content is as low as possible, and 0% is acceptable, but reducing the S content to less than 0.0001% significantly increases refining costs. Therefore, the S content may be set to 0.0001% or more, or 0.001% or more.
[0021] N: 0~0.0100% Nitrogen (N) is an impurity. N forms coarse nitrides that deteriorate the workability, wear resistance, and toughness of steel plates. Therefore, the N content is set to 0.0100% or less. The N content is preferably as low as possible, and 0% is acceptable, but reducing the N content to less than 0.0001% significantly increases refining costs. Therefore, the N content may be set to 0.0001% or more.
[0022] Remainder: Fe and impurities The balance of the chemical composition of the high carbon steel sheet according to this embodiment may be Fe and impurities. Alternatively, instead of a part of Fe, one or more optional elements selected from the group consisting of Ni, Cu, Co, Nb, Ti, V, B, Sn, W, Ca, and REM may be contained. When the following optional elements are not contained, the content of each optional element is 0%. Examples of impurities include elements that are allowed to be present within a range that does not impair the properties of the high carbon steel sheet according to the present embodiment and that are introduced from steel raw materials or scrap and / or during the steelmaking process. However, among the impurities, P, S, and N in particular are controlled within the above ranges.
[0023] Ni: 0 to 3.000% Ni is an element that has the effect of improving the hardenability of steel and increasing its strength. Therefore, Ni may be contained as necessary. In order to obtain the effect of improving hardenability by Ni, the Ni content is preferably 0.010% or more. On the other hand, if the Ni content is too high, segregation deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, when Ni is contained, the Ni content is set to 3.000% or less.
[0024] Cu: 0 to 3.000% Cu is an element that has the effect of improving the hardenability of steel and increasing its strength. Therefore, Cu may be contained as necessary. In order to obtain the effect of improving the hardenability by Cu, the Cu content is preferably 0.010% or more. On the other hand, if the Cu content is excessive, segregation deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing, so if Cu is contained, the Cu content is set to 3.000% or less.
[0025] Co: 0 to 3.000% Co is an element that has the effect of improving the hardenability of steel and increasing its strength. Therefore, Co may be contained as necessary. In order to obtain the effect of improving the hardenability by Co, the Co content is preferably 0.010% or more. On the other hand, if the Co content is too high, segregation deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, when Co is contained, the Co content is set to 3.000% or less.
[0026] Nb: 0 to 1.000% Nb is an element that has the effect of increasing the strength of steel by refining crystal grains. Therefore, Nb may be contained as necessary. In order to obtain the effect of refining crystal grains by Nb, the Nb content is preferably 0.010% or more. On the other hand, if the Nb content is excessive, segregation deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing, so when Nb is contained, the Nb content is set to 1.000% or less.
[0027] Ti: 0 to 1.000% Ti is an element that has the effect of increasing the strength of steel by refining crystal grains. Therefore, Ti may be contained as necessary. In order to obtain the effect of refining crystal grains by Ti, the Ti content is preferably 0.010% or more. On the other hand, if the Ti content is too high, segregation will deteriorate the workability of the steel sheet and the toughness and wear resistance of the parts after processing, so if Ti is contained, the Ti content is set to 1.000% or less.
[0028] V: 0~1.0000% V is an element that has the effect of increasing the strength of steel by refining crystal grains. Therefore, V may be contained as necessary. In order to obtain the effect of refining crystal grains by V, the V content is preferably 0.0010% or more. On the other hand, if the V content is excessive, segregation deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, if V is contained, the V content is set to 1.0000% or less.
[0029] B: 0~0.0100% B is an element that segregates at the grain boundaries to improve the strength of the grain boundaries and thereby increase the strength of the steel. Therefore, B may be contained as necessary. In order to obtain the effect of increasing the strength due to B, the B content is preferably 0.0005% or more. On the other hand, if the B content is excessive, segregation deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, if B is contained, the B content is set to 0.0100% or less.
[0030] Sn: 0 to 1.000% Sn is an element that deoxidizes molten steel to further improve the soundness of the steel and improve the workability of the steel sheet. Therefore, Sn may be contained as necessary. In order to obtain the effect of improving the workability by Sn, the Sn content is preferably 0.001% or more. On the other hand, if the Sn content is too high, coarse oxides are generated, which deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, if Sn is contained, the Sn content is set to 1.000% or less.
[0031] W: 0~1.000% W is an element that deoxidizes molten steel to further improve the soundness of the steel and improve the workability of the steel sheet. Therefore, W may be contained as necessary. In order to obtain the effect of W in improving the workability, the W content is preferably 0.001% or more. On the other hand, if the W content is excessive, coarse oxides are generated, which deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, if W is contained, the W content is set to 1.000% or less.
[0032] Ca: 0 to 0.3000% Ca is an element that deoxidizes molten steel to further improve the soundness of the steel and improve the workability of the steel sheet. Therefore, Ca may be contained as necessary. In order to obtain the effect of improving the workability by Ca, the Ca content is preferably 0.0001% or more, and more preferably 0.0100% or more. On the other hand, if the Ca content is excessive, coarse oxides are generated, which deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, if Ca is contained, the Ca content is set to 0.3000% or less.
[0033] REM: 0~0.300% REM is an element that deoxidizes molten steel to further improve the soundness of the steel and improve the workability of the steel sheet. Therefore, REM may be contained as necessary. In order to obtain the effect of improving the workability by REM, the REM content is preferably 0.001% or more. On the other hand, if the REM content is too high, coarse oxides are generated, which deteriorates the workability of the steel sheet and the toughness and wear resistance of the parts after processing. Therefore, if REM is contained, the REM content is set to 0.300% or less. REM is a general term for 17 elements in total consisting of Sc (scandium), Y (yttrium) and lanthanoid series elements, and the REM content means the total amount of the above elements. REM is often contained using misch metal, but in addition to La (lanthanum) and Ce (cerium), lanthanoid series elements may also be contained in combination. Even in such cases, the high carbon steel sheet according to this embodiment exhibits excellent workability. Furthermore, even if metallic REM such as metallic La and Ce is contained, the high carbon steel sheet according to this embodiment exhibits excellent workability.
[0034] The above-mentioned chemical compositions may be measured by a general analytical method. For example, they may be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). C and S may be measured using a combustion-infrared absorption method, and N may be measured using an inert gas fusion-thermal conductivity method.
[0035] Next, the microstructure of the high carbon steel sheet according to this embodiment will be described. <The microstructure is composed of 70 to 95% ferrite and carbides in terms of area ratio, and the average aspect ratio of the carbides is 3.0 or less and the average equivalent circle diameter is 0.40 to 2.00 μm> The high carbon steel sheet in this embodiment has a microstructure consisting of ferrite with an area ratio of 70 to 95%, and the remainder being carbide. In the microstructure, if the area ratio of ferrite is less than 70%, the strength of the steel sheet becomes too high and the workability deteriorates.The area ratio of ferrite is preferably 75% or more, and more preferably 80% or more. On the other hand, if the area ratio of ferrite exceeds 95%, the carbon concentration in the carbide becomes high and the workability deteriorates. Therefore, the area ratio of ferrite is set to 95% or less. The area ratio of ferrite is preferably 93% or less, and more preferably 90% or less.
[0036] In the microstructure of the high carbon steel sheet according to the present embodiment, the remainder other than ferrite is carbide. If the area ratio of carbide is less than 5%, the carbon concentration in the carbide becomes high, and the workability is deteriorated. On the other hand, if the area ratio of carbide is more than 30%, the workability is deteriorated. In addition, as a result of the inventors' investigation of carbides, it was found that in high carbon steel sheets having a C content of 0.60% or more, the steel sheet is softened and workability is improved by spheroidizing the carbides and increasing their size. More specifically, it was found that the steel sheet is softened if the average aspect ratio of the carbides is 3.0 or less and the average equivalent circle diameter is 0.40 μm or more. Therefore, the average aspect ratio of the carbides is set to 3.0 or less and the average equivalent circle diameter is set to 0.40 μm or more. The average aspect ratio is preferably 2.7 or less, more preferably 2.5 or less. The average equivalent circle diameter is preferably 0.70 μm or more. On the other hand, if the average equivalent circle diameter of the carbide exceeds 2.00 μm, the workability deteriorates. Therefore, the average equivalent circle diameter of the carbide is set to 2.00 μm or less. The average equivalent circle diameter is preferably 1.60 μm or less, and more preferably 1.40 μm or less. In the chemical composition of the high carbon steel plate according to this embodiment, the carbides of the above sizes are, for example, cementite.
[0037] In the high carbon steel sheet according to the present embodiment, it is preferable that 70% or more of the above-mentioned carbides are present in the grain boundaries in terms of the number ratio. By increasing the ratio of the carbides present in the grain boundaries, the workability is improved. The ratio of the carbides present in the grain boundaries is preferably 80% or more, more preferably 90% or more.
[0038] In the high carbon steel sheet according to the present embodiment, carbides having a small average aspect ratio and large size as described above can be obtained by annealing a steel sheet having a microstructure mainly composed of martensite. The reason for this is considered as follows. In general, the diffusion of alloying elements is faster at grain boundaries than at volume diffusion. Therefore, when a structure having a high grain boundary density is annealed, the diffusion of alloying elements is faster. Martensite is a structure composed of a fine structure such as laths and has a high grain boundary density. By annealing martensite, more martensite precipitates at the grain boundaries than when other structures are annealed, and the growth rate of carbides becomes faster, which is thought to increase the size of cementite. This finding was newly discovered by the present inventors.
[0039] The structure fraction, average aspect ratio, average equivalent circle diameter, and precipitation position of carbides can be measured by the following methods. First, a sample is cut out from a high carbon steel plate so that a cross section perpendicular to the surface (cross section of plate thickness) can be observed. The length of the sample may be about 10 mm, depending on the measuring device. The cross section is polished and corroded to measure the area ratio of ferrite and carbide, the precipitation position of carbide, the average aspect ratio, and the average equivalent circle diameter. Here, a specific method of polishing is given below. For example, the cross section is polished using silicon carbide paper with a grain size of 600 (#600) to 1500 (#1500), and then the cross section is finished to a mirror surface using a dilution liquid such as alcohol or a liquid in which diamond powder with a grain size of 1 to 6 μm is dispersed in pure water. The corrosion is not particularly limited as long as it is a method that can observe the shape and precipitation position of carbide. For example, etching with a saturated picric acid-alcohol solution may be performed as a means of corroding the grain boundary between the carbide and the base steel. Alternatively, a method such as constant potential electrolytic etching using a non-aqueous electrolyte (Fumio Kurosawa et al., Journal of the Japan Institute of Metals, 43, 1068, (1979)) may be used to remove about several micrometers of the base steel, leaving only the carbide. Then, a scanning electron microscope was used to measure the thickness of the sample at a position 1 / 4 of the thickness from the surface. 2 The above-mentioned range is observed at a magnification of 5000 times. In the observed region, the area of each carbide is measured, and the diameter when the average area per particle is approximated by a circle is taken as the average equivalent circle diameter of the carbides. In addition, the lengths of the major and minor axes of each carbide in the observation area are measured, the aspect ratio (major axis length / minor axis length) of each carbide is calculated, and these are averaged to obtain the average aspect ratio. In addition, a thermal field emission scanning electron microscope (e.g., JEOL JSM-7001F) was used to measure the thickness of the sample at 1 / 4 (1 / 4 of the thickness from the surface in the thickness direction) at a distance of 10,000 μm. 2The observation is performed in five visual fields, the ratio of the area occupied by ferrite is calculated for each of the five visual fields, and the average of these is taken as the area ratio of ferrite. The ratio of the area occupied by carbide is calculated for each of the five visual fields, and the average of these is taken as the area ratio of carbide. Ferrite is observed in a thermal field emission scanning electron microscope as a dark contrast region that does not include a substructure. On the other hand, carbide is observed with a bright contrast. Therefore, ferrite and carbide can be separated from each other based on the difference in contrast of the image taken with the thermal field emission scanning electron microscope. In addition, the precipitation positions of all carbides included in the observed field of view are observed. The ratio of carbides precipitated at the grain boundaries of ferrite among all carbides is calculated. The average value of the ratio of carbides precipitated at the grain boundaries of ferrite in the above five fields of view is regarded as the ratio of carbides formed at the grain boundaries of ferrite among all carbides (i.e., the ratio of the number of carbides present at the grain boundaries of ferrite among all carbides).
[0040] In the high carbon steel sheet according to this embodiment, the {100} <011> ~{223} <110> The average value of the X-ray random intensity ratio of the orientation group is preferably 7.0 or less, more preferably 6.0 or less, and further preferably 4.0 or less. There is no particular lower limit, but in practical operation, it is 0.5. Ferrite {100} <011> ~{223} <110> When the average value of the X-ray random intensity ratio of the orientation group is 7.0 or less, by appropriately controlling the heat treatment conditions, the parts obtained by carrying out the heat treatment and processing can have excellent toughness.
[0041] The texture of ferrite is mainly controlled by the chemical composition of the steel sheet and the manufacturing conditions. Specifically, by setting the coiling temperature at 300°C or less, the texture of the hot-rolled steel sheet can be controlled to be mainly martensite. Martensite is composed of multiple fine crystal grains called martensite laths, which promotes randomization of the crystal orientation. Therefore, by controlling the texture to be mainly martensite, the {100} of the crystal grains can be controlled to be mainly martensite. <011> ~{223} <110> The development of orientation groups can be suppressed. <011> ~{223} <110> By suppressing the development of the orientation group, the ferrite that is generated during the subsequent annealing has a {100} <011> ~{223} <110> The development of orientation groups is suppressed, and the {100} <011> ~{223} <110> The average value of the X-ray random intensity ratio of the orientation group can be set to 7.0 or less. The crystal orientation is usually expressed as [hkl] or {hkl} for the orientation perpendicular to the plate surface, and (uvw) or {uvw} for the orientation parallel to the rolling direction. <uvw>Display it as {hkl}, <uvw>is a general term for the equivalent plane. The {100} <011> ~{223} <110> The main directions included in the group are {100} <011> , {116} <110> , {114} <110> , {113} <110> , {112} <110> , {335} <110> , and {223} <110> It is.
[0042] The texture of ferrite can be measured using EBSD in the following way. First, a sample is cut out from a high carbon steel plate so that a cross section perpendicular to the surface (cross section through the plate thickness) can be observed. The length of the sample depends on the measuring device, but it may be about 10 mm to 25 mm. 2 The range is measured at a measurement interval of 5.0 μm using electron backscattering diffraction (EBSD) to obtain crystal orientation information. Here, the EBSD analysis is performed, for example, using an apparatus consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 detector) at an electron beam acceleration voltage of 15 kV to 25 kV and an analysis speed of 200 to 300 points / second. Using the "TEXTURE" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device, the three-dimensional texture calculated by the series expansion method is calculated from the obtained crystal orientation information. Next, using the "ODF" function, the intensities of (001)[1-10], (116)[1-10], (114)[1-10], (113)[1-10], (112)[1-10], (335)[1-10], and (223)[1-10] in the φ2=45° cross section of the three-dimensional texture can be used as the X-ray random intensity ratio of the ferrite grains. {100} <011> ~{223} <110> The average value of the orientation group is the arithmetic mean of the above orientations. If it is not possible to obtain the intensities of all the above orientations, for example, {100} <011> , {116} <110> , {114} <110> , {112} <110> , {223} <110> In crystallography, the orientation "-1" is officially written as "1" with an upper bar, but in this embodiment, due to limitations in the description, it is written as "-1".
[0043] The high carbon steel sheet according to the present embodiment may have a plating layer formed on the surface for the purpose of improving the corrosion resistance of a part obtained through processing and heat treatment. The plating layer may be either an electroplated layer or a hot-dip plated layer. The electroplated layer includes, for example, an electrogalvanized layer, an electrolytic Zn-Ni alloy plating layer, and the like. The hot-dip plated layer includes, for example, a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, a hot-dip aluminum plating layer, a hot-dip Zn-Al alloy plating layer, a hot-dip Zn-Al-Mg alloy plating layer, a hot-dip Zn-Al-Mg-Si alloy plating layer, and the like. The coating weight of the plating layer is not particularly limited and may be a general coating weight.
[0044] The plate thickness of the high carbon steel plate according to this embodiment is not particularly limited, but is, for example, 2.0 mm to 6.0 mm.
[0045] A preferred method for producing the high carbon steel sheet according to this embodiment will be described. The high carbon steel sheet in this embodiment can be manufactured by a manufacturing method including the following steps. (I) A hot rolling process in which a slab having a specified chemical composition is heated and hot rolled to obtain a hot-rolled steel sheet. (II) Winding process for winding hot-rolled steel sheets (III) An annealing process for annealing hot-rolled steel sheets after the coiling process, or cold-rolled steel sheets obtained by cold-rolling hot-rolled steel sheets. Preferred conditions for each step are described below. For steps and conditions not described below, known conditions can be used.
[0046] <Hot rolling process> In the hot rolling process, the slab having the above-mentioned chemical composition is made into a hot-rolled steel sheet. Although the hot rolling conditions are not limited, it is preferable to heat the slab to a temperature of 1200°C or more and less than 1350°C, and hot roll the heated slab to a finishing temperature of 800°C or more and 1150°C or less. A heating temperature of less than 1200°C is not preferred because the workability of the steel sheet and the toughness and wear resistance of the steel sheet when used in parts may deteriorate, while a heating temperature of 1350°C or higher is not preferred because the grain growth of austenite is promoted too much, causing the texture of martensite to develop and making it impossible to control the texture. Moreover, if the finishing temperature is less than 800° C., the martensite texture develops and it becomes difficult to control the texture to a desired one, which is undesirable. Moreover, if the finishing temperature exceeds 1150°C, the grain growth of austenite is promoted too much, and the texture of martensite develops, making it impossible to control the texture to a desired level, which is undesirable.
[0047] <Winding process> In the coiling process, in order to make the microstructure mainly martensite, the hot-rolled steel sheet after the hot rolling process is cooled to a temperature range of 300°C or less at an average cooling rate of 5°C / sec or more, and coiled at that temperature range. If the average cooling rate is less than 5° C. / sec or the coiling temperature exceeds 300° C., ferrite and pearlite are generated, and a martensite-based structure cannot be obtained. In this case, carbides with a predetermined average aspect ratio and average equivalent circle diameter cannot be obtained after the subsequent annealing. Furthermore, if the average cooling rate is less than 5°C / sec, or the coiling temperature exceeds 300°C, the ferrite texture develops. Although the lower limit of the coiling temperature is not particularly set, since it is difficult to maintain the temperature below room temperature in actual operation, room temperature (about 25°C) is the substantial lower limit. In order to ensure that 70% or more of the carbides after annealing are present at the grain boundaries, it is preferable to set the cooling rate to 5°C / s or more and the coiling temperature to 290°C or less. The coiling temperature is more preferably 280°C or less, and even more preferably 250°C or less. The upper limit of the average cooling rate is not particularly set, but may be set to 500° C. / sec or less in consideration of cracking during quenching.
[0048] <Annealing process> In the annealing process, a high carbon steel sheet having a structure mainly composed of martensite is annealed by holding it at a temperature of 600°C to 730°C for 1.0 hour or more. As mentioned above, the diffusion of alloying elements is faster through grain boundaries than through the entire body, so that annealing a structure with a high grain boundary density such as martensite accelerates the diffusion of alloying elements. By making the structure before annealing mainly martensite and further setting the temperature and time of the annealing process appropriately, carbides precipitate at the grain boundaries during annealing, promoting the grain growth of the carbides and increasing the carbide diameter, and further controlling the carbides to a desired average aspect ratio. If the annealing temperature is less than 600° C., the formation of carbides is delayed, making it impossible to obtain a predetermined amount of carbides. Therefore, the annealing temperature is set to 600° C. or higher. The annealing temperature is preferably 650° C. or higher. If the annealing time is less than 1.0 hour, the spheroidization of the carbides is delayed, and the desired average particle size and average aspect ratio cannot be obtained. Therefore, the annealing time is set to 1.0 hour or more, and preferably 2.0 hours or more. If the annealing temperature exceeds 730° C., the ferrite transformation is delayed and the desired amount of ferrite cannot be obtained, so the annealing temperature is set to 730° C. or lower, and preferably 710° C. or lower. Although there is no upper limit to the annealing time, if it exceeds 100 hours, only ferrite grains having a specific crystal orientation grow preferentially, and it is not possible to obtain a desired texture, so the annealing time is preferably 100 hours or less, and more preferably 90 hours or less. In the above-mentioned annealing process, the annealing atmosphere gas may be at least one of gases such as nitrogen and hydrogen, or an inert gas such as argon. In addition, there is no problem if the atmosphere gas contains a small amount of gas such as oxygen. The atmosphere gas in the heating furnace used in the annealing process can be controlled, for example, by introducing the above-mentioned gas and appropriately measuring the gas concentration in the heating furnace. The hot-rolled steel sheet to be annealed may be a hot-rolled steel sheet as it is after coiling, or may be a hot-rolled steel sheet that has been separately annealed (hot-rolled steel sheet annealing). The cold-rolled steel sheet may be a cold-rolled steel sheet obtained by annealing a hot-rolled steel sheet (hot-rolled steel sheet annealing) and then cold rolling the same. In this case, the conditions for the hot-rolled steel sheet annealing and cold rolling are not limited and may be any known conditions.
[0049] <Plating process> A plating layer may be formed on the surface of the obtained high carbon steel sheet. The plating method is not limited, and may be performed under known conditions depending on the plating layer to be formed. EXAMPLES
[0050] Slabs having the chemical compositions shown in Tables 1A to 1F were hot-rolled and coiled under the conditions shown in Tables 2A to 2C to obtain hot-rolled steel sheets of 2.0 to 6.0 mm. The hot-rolled steel sheets were then annealed under the conditions shown in Tables 2A to 2C to obtain steel sheets (high carbon steel sheets) Nos. S1 to S119 and S122 to S148. The hot-rolled steel sheets were cold-rolled and then annealed under the conditions shown in Tables 2A to 2C to obtain steel sheet No. S120. The hot-rolled steel sheets were hot-rolled annealed and cold-rolled, and then annealed under the conditions shown in Tables 2A to 2C to obtain steel sheet No. S121. In the annealing process, the annealing atmosphere of S1 to S145 was a mixed atmosphere of nitrogen and hydrogen, S146 was a nitrogen atmosphere, S147 was a hydrogen atmosphere, and S148 was an argon atmosphere. In addition, some of the steel sheets were plated.
[0051] [Table 1A]
[0052] [Table 1B]
[0053] [Table 1C]
[0054] [Table 1D]
[0055] [Table 1E]
[0056] [Table 1F]
[0057] [Table 2A]
[0058] [Table 2B]
[0059] [Table 2C]
[0060] The area ratio of ferrite and carbide, the average aspect ratio of carbide, the average equivalent circle diameter of carbide, the ratio of carbide existing at grain boundaries, and the {100} <011> ~{223} <110> The average value of the X-ray random intensity ratio of the orientation group was calculated. The results are shown in Tables 3A to 3C.
[0061] Furthermore, the workability of these steel sheets was evaluated by Vickers hardness. The Vickers hardness was measured by the following method. Samples were cut out so that a cross section perpendicular to the surface (cross section of the plate thickness) could be observed from any position of the steel plate after annealing. The size of the sample was such that 10 mm could be observed in the rolling direction. The cross section of the sample was polished using silicon carbide paper of #600 to #1500, and then finished to a mirror surface using a liquid in which diamond powder with a grain size of 1 to 6 μm was dispersed in a dilution liquid such as alcohol and pure water. The hardness of the mirror-finished cross section was measured at a position 1 / 4 of the plate thickness in the direction parallel to the plate surface (rolling direction) with a load of 5 kgf at intervals of at least three times the indentation using a micro Vickers hardness tester. A total of 20 points were measured, and the average value was taken as the Vickers hardness of the steel plate after annealing. When the hardness of the steel sheet after annealing was 220 Hv or less, it was judged to have excellent workability and to pass the test.
[0062] [Table 3A]
[0063] [Table 3B]
[0064] [Table 3C]
[0065] As can be seen from Tables 1A to 3C, the inventive examples had a predetermined chemical composition, and the microstructure consisted of 70 to 95% ferrite and carbides in terms of area ratio, with the carbides having an average aspect ratio of 3.0 or less and an average equivalent circle diameter of 0.40 to 2.00 μm. As a result, excellent workability was obtained.
[0066] In contrast, in the comparative examples S11, S18, S26, S27, S33, S41, S49, S53, S57, S61, S109, S118, S130, S136, and S137, one or more of the chemical composition, the structural fraction of ferrite and carbide, the average aspect ratio of carbides, and the average equivalent circle diameter were outside the range of the present invention, and the workability was poor.< / uvw> < / uvw>
Claims
1. In mass percent, C: 0.60-1.30%, Si: 0.010-0.500%, Mn: 0.35-1.00%, Al: 0.0010-0.0500%, Cr: 0.010-0.600%, Mo: 0.005-0.050%, P: 0-0.100%, S: 0-0.100%, N: 0 to 0.0100%, Ni: 0-3.000%, Cu: 0-3.000%, Co: 0-3.000%, Nb: 0 to 1.000%, Ti: 0 to 1.000%, V: 0 to 1.0000%, B: 0 to 0.0100%, Sn: 0-1.000%, W: 0-1.000%, Ca: 0-0.3000%, REM: 0-0.300%, The balance: Fe and impurities, having a chemical composition consisting of The microstructure is composed of 70 to 95% ferrite and carbide by area ratio, The carbide has an average aspect ratio of 3.0 or less and an average equivalent circle diameter of 0.40 to 2.00 μm, In terms of number ratio, 70% or more of the carbides are present at grain boundaries. A high carbon steel plate characterized by:
2. the average value of the X-ray random intensity ratio of the {100}<011> to {223}<110> orientation group of the ferrite is 7.0 or less; The high carbon steel sheet according to claim 1 .
Citation Information
Patent Citations
High-carbon hot-rolled steel sheet and manufacturing method therefor
JP2006097109A
High-carbon cold-rolled steel sheet superior in workability, and manufacturing method therefor
JP2007031762A
High-carbon hot-rolled steel sheet and process for producing the same
JP2007039796A
Method for manufacturing high-carbon cold-rolled steel sheet superior in workability, and high-carbon cold-rolled steel sheet
JP2007119883A
Steel for induction hardening with excellent cold workability, and its manufacturing method
JP2007131907A
